Electricity Procurement Strategies under Supply Disruption and Price Fluctuation - Jie Tan; Qin Zhong (Complexity)
Improving the reliability of electricity supply is closely related to the national industrial economy and people’s livelihood. When procuring electricity, the large consumer faces the risk of insufficient electricity supply. Such insufficiency may be caused by the supply disruption of the upstream electricity generator and the fluctuation of electricity prices in the electricity pool. We establish an expected cost model for the large consumer and a revenue model for the electricity generator by introducing robustness and opportunity functions to analyse the impact of supply disruption and price fluctuation on both members. Then, we obtain the optimal reliability level and subsidy rate. Our analytical results reveal the following points: (1) During an electricity price fluctuation, the sufficient and necessary condition for the large consumer to expect high robustness of his own decision-making is to pay a high cost. (2) The high uncertainty of electricity price leads to less revenue for the electricity generator; thus, the electricity generator should perform well in price forecasting. (3) Without disruption risk, the electricity generator is reliable. Furthermore, the electricity pool is unreliable from the perspective of price. However, the electricity supply of the electricity generator is no longer reliable when considering disruption risk, whereas the electricity pool is reliable because the large consumer is tolerant of price fluctuation under this circumstance. Moreover, the impacts of market uncertainty and players’ attributes on the optimal strategies are explored.